2015
DOI: 10.17656/jsmc.10078
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Rhomboid Flap and Z-Plasty in Pilonidal Sinus Surgery

Abstract: Background There are controversies about the etiology and management of pilonidal sinus. The numbers of techniques are testament in treating pilonidal sinus (PNS) and no single procedure is superior in all aspects. Objectives The Purpose of this study was to evaluate two operative procedures regarding its complications including recurrences of the disease. Methods The medical records of 40 patients in whom the Rhomboid Flap and Z-Plasty techniques were applied for reconstruction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Excision with primary closure is another alternative surgical therapy. The latter has the advantage of early cure rate, less job absence, more patient satisfaction and being less costly [20] . All surgical therapies put the patient at risk of morbidity and long time work absence, so they don’t seem to be ideal management strategy [13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excision with primary closure is another alternative surgical therapy. The latter has the advantage of early cure rate, less job absence, more patient satisfaction and being less costly [20] . All surgical therapies put the patient at risk of morbidity and long time work absence, so they don’t seem to be ideal management strategy [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Not like sacrococcigeal PNS, iPNS has least technical problem with primary closure. The former needs flap for which countless techniques have been proposed in the literature [20] . However, flap has never been recommended for primary closure of iPNS.…”
Section: Discussionmentioning
confidence: 99%
“…A preferable surgical therapy includes excision with primary closure, which is more reliable than the previous one due to less time consumption, positive cure rate, less costs, and more patient satisfaction [ 12 ]. Non-operative therapies like phenol injection, laser therapy, and ointment sometimes can be used but some studies reported recurrence, failure, and complication development after phenol injection [ [13] , [14] , [15] ]. Some studies encourage treatment with surgical therapy (excision and primary closure) due to recurrence after aspiration and medical treatment or slow response of the abscess to antibiotics [ 1 , 10 ].…”
Section: Discussionmentioning
confidence: 99%